2009
DOI: 10.1111/j.1540-6237.2009.00619.x
|View full text |Cite
|
Sign up to set email alerts
|

Political Culture, Public Opinion, and Policy (Non)Diffusion: The Case of Gay‐ and Lesbian‐Related Issues in Arkansas*

Abstract: Just after three in four Arkansas voters endorsed a state constitutional amendment barring state recognition of same-sex marriages, a comprehensive state-level survey allowed a closer look into the attitudes of Arkansans on a variety of gay- and lesbian-related issues. When placed in the context of Arkansas's political culture and ideological patters, this serves as a case study of the relationship between public opinion, specific policy issues, and the diffusion (or nondiffusion) of policies in an individual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 17 publications
4
15
0
Order By: Relevance
“…Consistent with other studies, our results demonstrated large basic differences between liberals and conservatives on abortion and same-sex marriage attitudes (Barth & Parry, 2009;Brewer & Wilcox, 2005;Chambers et al, 2006), but with notable qualifications. Strongly identified liberals and conservatives were more likely than those weakly identified to endorse differentiated and polarized attitudes.…”
Section: The Effects Of Group Identity Strength and Attitude Strengthsupporting
confidence: 94%
See 2 more Smart Citations
“…Consistent with other studies, our results demonstrated large basic differences between liberals and conservatives on abortion and same-sex marriage attitudes (Barth & Parry, 2009;Brewer & Wilcox, 2005;Chambers et al, 2006), but with notable qualifications. Strongly identified liberals and conservatives were more likely than those weakly identified to endorse differentiated and polarized attitudes.…”
Section: The Effects Of Group Identity Strength and Attitude Strengthsupporting
confidence: 94%
“…Building on the notion that liberals and conservatives may selectively hold polarized attitudes on a smaller set of issues than all those generally connected to these identities, this set of issues could vary from person to person and may comprise those that they consider highly relevant to their personal identification as liberal or conservative. Although positions on abortion and same-sex marriage are strongly tied to liberalism and conservatism in general (Barth & Parry, 2009;Brewer & Wilcox, 2005;Chambers et al, 2006), individuals in our study who perceived them as irrelevant to how they personally identified as such did not hold differentiated attitudes from one another. For these individuals, the irrelevance of the issue to their identity may have minimized the threat this posed to their identity or concern over misclassification on account of the specific issue.…”
Section: The Additional Effect Of Issue Relevance: Connecting Issues mentioning
confidence: 61%
See 1 more Smart Citation
“…Issues related to sexual orientation, such as same‐sex marriage, are becoming more prominent in social and political discourse. Individuals and political groups have framed their support for or opposition to related policies in different ways, at times based on civil rights, religious views, or traditional norms (Barth & Parry, 2009; Brewer & Wilcox, 2005; Miceli, 2005; Olson, Cadge, & Harrison, 2006). Yet, few studies have tested the extent to which these frameworks uniquely contribute to individuals' positions or how certain ideologies operate in association with or independent from sexual prejudice (i.e., negative attitudes toward sexual minorities such as gay men and lesbians; Herek, 2000).…”
mentioning
confidence: 99%
“…Several references to gay and lesbian foster parents have been made in recent literature (Rimalower & Caty, 2009), indicating their strong presence within the foster family population (Downs & James, 2006), challenges faced in public perception (Barth & Parry, 2009), reception by the child welfare system (Logan & Sellick, 2007;Rawsthorne, 2009), including foster parent supports and services that are sensitive to their realities (Patrick, 2006;Riggs & Augoustinos, 2009). Their resilience (Oswald, 2002) and caregiving practices (Craig-Oldsen, Craig, & Morton, 2006) have been the subject of different studies on fostering satisfaction and retention, but no studies of values, beliefs, and traditions were located.…”
Section: Gender and Sexual Orientationmentioning
confidence: 96%